Acknowledging the Head, Heart, Hands and Feet: Research with Refugees and People Seeking Asylum in Higher Education. (1st May 2019) - Reimer, Kristin; Kaukko, Mervi; Dunwoodie, Karen; Wilkinson, Jane; Webb, Sue
In this article, we focus on the ethical complexities of conducting research with people from refugee and asylum-seeking backgrounds. We provide a critical heart, hands and feet of research ethics. In this metaphor, the head refers to the rational approach to ethics, heart to the emotional and intuitive response to ethics, hands to the practical engagement with ethics and feet to the way forward. We argue that traditional and ethical guidelines prescribed by higher education institutions are not sufficient to prepare researchers for the unique complexities of working with refugees and people seeking asylum. Instead, alongside such prescribed and rational approaches, we must also engage the heart, hands and feet. Our aim is to consider how research conducted with students from refugee and asylum-seeking backgrounds can be approached in a holistic and ethical manner.